Engineering Asset Lifecycle Management Proceedings of the 4th World Congress on Engineering Asset Management (WCEAM 2009), 28-30 September 2009 - Kiritsis, Dimitris; Emmanouilidis, Christos; Koronios, Andy.; Mathew, Joseph; SpringerLink (Online service) (London : Springer London, 2010)
Engineering Asset Management discusses state-of-the-art trends and developments in the emerging field of engineering asset management as presented at the Fourth World Congress on Engineering Asset Management (WCEAM). It is an excellent reference for practitioners, researchers and students in the multidisciplinary field of asset management, covering such topics as asset condition monitoring and intelligent maintenanc; asset data warehousing, data mining and fusion; asset performance and level-of-service models; design and life-cycle integrity of physical assets; deterioration and preservation models for assets; education and training in asset management; engineering standards in asset management; fault diagnosis and prognostics; financial analysis methods for physical assets; human dimensions in integrated asset management; information quality management; information systems and knowledge management; intelligent sensors and devices; maintenance strategies in asset management; optimisation decisions in asset management; risk management in asset management; strategic asset management; and sustainability in asset management.
EURENSEAM - 1 - Strategic Engineering Asset Management -- Transport, Building and Structural Asset Management -- Lifecycle & Sustainability Considerations Of Physical Assets -- EURENSEAM - 2 - Strategic Engineering Asset Management -- Transport, Building and Structural Asset Management -- Technologies For Asset Data Management, Warehousing & Mining -- EFNMS - Engineering Asset Management in Europe -- Decision Support & Optimisation Methods & Tools -- Maintenance for Sustainable Manufacturing - 1 -- Strategic asset management for sustainable business -- Advanced Maintenance Strategies (RCM,CBM,RBI) -- Maintenance for Sustainable Manufacturing - 2 -- Planning, Scheduling & Performance Monitoring -- Decision Support & Optimisation Methods & Tools -- Maintenance for Sustainable Manufacturing - 3 - Education & Training -- Advanced Maintenance Strategies -- Condition Monitoring, Diagnostics & Prognostics -- Emerging Technologies in EAM -- Condition Monitoring, Diagnostics & Prognostics -- e-Maintenanance -- Policy, Regulations, Practices & Standards For Asset Management -- Condition Monitoring, Diagnostics & Prognostics -- Technologies For Asset Data Management, Warehousing & Mining -- Advanced Maintenance Strategies (RCM,CBM,RBI) -- Condition Monitoring, Diagnostics & Prognostics -- Workshop for e-training in Maintenance Management (HMS, M4SM, iLearn2Main) -- Safety, health and risk management in EAM -- Condition Monitoring, Diagnostics & Prognostics.
Keywords: Engineering; Industrial engineering; Engineering economy; System safety; Telecommunication; Industrial organization (Economic theory).; Engineering; Engineering Economics, Organization, Logistics, Marketing; Industrial and Production Engineering; Quality Control, Reliability, Safety and Risk; Signal, Image and Speech Processing; Communications Engineering, Networks; Industrial Organization